Ժամանակավոր կառավարության արտաքին քաղաքականությունը և Թուրքահայաստանը - Մարուքյան, Ա. (ՀՀ ԳԱԱ հրատ.)
После Февральской революции власть перешла к Временному правительству, которая находилась под непрерывным дипломатическим давлением со стороны союзных держав. Временное правительство сделало несколько попыток восстановить положения соглашения Сайка-Пико в отношении раздела Турции и в частности -Западной Армении. After the February revolution the power in Russia passed to Temporary government, which was upon unbroken diplomatic pressure of allied powers. The Temporary government made some attempts to restore the positions of Saics-Pico Agreement about the division of Turkey and particularly of the Western Armenia, but the allied powers declined even the question of autonomy of the Western Armenia, suggested by Russia.
Keywords: Modern History